Answer:
[tex]\large\boxed{-6+6\sqrt3i=12\left(\cos\dfrac{2\pi}{3}+i\sin\dfrac{2\pi}{3}\right)}[/tex]
Step-by-step explanation:
Look at the picture.
The trigonometric form of a complex number:
[tex]z=|z|(\cos\alpha+i\sin\alpha)[/tex]
where:
[tex]|z|=\sqrt{a^2+b^2}\\\\\cos\alpha=\dfrac{a}{|z|}\\\\\sin\alpha=\dfrac{b}{|z|}[/tex]
We have the complex number:
[tex]z=-6+6\sqrt3i\to a=-6,\ b=6\sqrt6[/tex]
Substitute:
[tex]|z|=\sqrt{(-6)^2+(6\sqrt3)^2}=\sqrt{36+108}=\sqrt{144}=12[/tex]
[tex]\cos\alpha=\dfrac{-6}{12}=-\dfrac{1}{2}\\\\\sin\alpha=\dfrac{6\sqrt3}{12}=\dfrac{\sqrt3}{2}[/tex]
Therefore
[tex]\alpha=\dfrac{2\pi}{3}[/tex]
Finally:
[tex]-6+6\sqrt3i=12\left(\cos\dfrac{2\pi}{3}+i\sin\dfrac{2\pi}{3}\right)[/tex]